2017
DOI: 10.1183/13993003.00083-2017
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline as a potential agent in the treatment ofMycobacterium abscessusinfections

Abstract: Bedaquiline as a potential agent in the treatment of Mycobacterium abscessus infections To the Editor: Mycobacterium abscessus is increasingly being recognised as a significant human pathogen, especially in patients with cystic fibrosis, and the specific M. abscessus subspecies seems to influence the clinical outcome [1]. The pulmonary manifestation of this nontuberculous mycobacteria (NTM) infection is one of the most difficult to treat forms, leading to substantial morbidity and mortality in this population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 15 publications
5
24
0
1
Order By: Relevance
“…Based on our data and those of others ( 14 , 15 , 17 ), bedaquiline showed a high antibacterial activity at a very low concentration (<0.1 mg/liter). In addition, bedaquiline can maintain a mean plasma concentration of 0.6 mg/liter at standard oral doses ( 18 ), and it can be extensively distributed to tissues, including the lungs, according to the pharmacokinetic studies ( 19 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on our data and those of others ( 14 , 15 , 17 ), bedaquiline showed a high antibacterial activity at a very low concentration (<0.1 mg/liter). In addition, bedaquiline can maintain a mean plasma concentration of 0.6 mg/liter at standard oral doses ( 18 ), and it can be extensively distributed to tissues, including the lungs, according to the pharmacokinetic studies ( 19 ).…”
Section: Discussionsupporting
confidence: 83%
“…New drugs, especially new anti-TB drugs, against M. abscessus infections have brought new hope for treating M. abscessus infections. With the advantages of oral delivery, bedaquiline has been considered as a prospective drug in the treatment of M. abscessus infections ( 17 ). Thus, clinical data for in vitro susceptibility of M. abscessus to bedaquiline are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…BDQ acts by targeting the c subunit of the essential F o F 1 ATP synthase (24)(25)(26)(27), and studies have also proposed that it may inhibit the ATP synthase via another mechanism involving the subunit of the enzyme, in addition to binding to its c subunit (28,29). BDQ exhibits very low MICs against various NTM, including M. abscessus clinical isolates from CF and non-CF patients (27,30,31), but despite being an excellent growth inhibitor at low doses, it lacks bactericidal activity against M. abscessus (27). Studies in immunocompromised mouse models led to conflictual conclusions, reporting, on the one hand, a benefit of BDQ in reducing bacterial loads in gamma interferon knockout mice (32) and, on the other hand, no decrease in the bacillary loads in the lungs or an inability to prevent death in nude mice (33).…”
mentioning
confidence: 99%
“…BDQ is a diarylquinoline approved by the U.S. Food and Drug Administration and the European Medicines Agency for the treatment of multidrug-resistant tuberculosis (10). We and others have recently shown that BDQ exhibits very low MIC values against NTM, including clinical M. abscessus strains from CF and non-CF patients (11)(12)(13). To determine the cooperative potential of BDQ with companion drugs for new treatment regimens against M. abscessus, evaluation of combinations of BDQ and other antimicrobials in synergism is necessary.…”
mentioning
confidence: 99%